2022
DOI: 10.29390/cjrt-2022-011
|View full text |Cite
|
Sign up to set email alerts
|

A survey of minimally invasive surfactant therapy in Canada

Abstract: Introduction Minimally invasive surfactant therapy (MIST) can be used to treat neonatal respiratory distress syndrome in neonatal intensive care units (NICUs). Clinical and institutional variances in MIST utilization persist globally with little published research regarding MIST utilization in Canada. Therefore, the objective of this study was to survey MIST utilization in NICUs in Canada. Methods An online survey was emailed to the 33 participating centres of Canadian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A recent survey of MIST use in Canada reported that 47% of centers using MIST utilize Angiocatheter to deliver surfactant, whereas 41% use purpose-built catheters. 20 Some centers still report the use of feeding tubes. Among the centers that do not use MIST, 22% cited the lack of availability of purpose-built catheters as the reason for the non-implementation of MIST.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of MIST use in Canada reported that 47% of centers using MIST utilize Angiocatheter to deliver surfactant, whereas 41% use purpose-built catheters. 20 Some centers still report the use of feeding tubes. Among the centers that do not use MIST, 22% cited the lack of availability of purpose-built catheters as the reason for the non-implementation of MIST.…”
Section: Discussionmentioning
confidence: 99%
“…MIST procedures that have been adopted in various countries often demonstrate practice variations, such as varying types of catheters, types of surfactants, choice of premedications, etc. [ 6 , 8 , 9 ]. The type of laryngoscope used to conduct MIST is now emerging to be another such procedural variation.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing application of VL for neonatal airway management, it is speculated that MIST techniques can be easily adapted for use with VL. In a Canadian survey, 47% of the neonatal intensive care units (NICUs) in Canada used VL for MIST procedures [ 8 ]. Recently, a quality improvement initiative showed the safety and efficacy of VL use in LISA [ 3 ].…”
Section: Introductionmentioning
confidence: 99%